Chinese American transnationalism : the flow of people, resources, and ideas between China and America during the exclusion era - Chan, Sucheng (Philadelphia, PA : Temple University Press, 2006)
The third volume in a trilogy that offers the most comprehensive account to date of the Chinese American experience during the exclusion era.
Defying exclusion : Chinese immigrants and their strategies during the exclusion era / Erika Lee -- Trading with Gold Mountain : Jinshanzhuang and networks of kinship and native place / Madeline Hsu -- Against all odds : Chinese female migration and family formation on American soil during the early twentieth century / Sucheng Chan -- Chinese herbalists in the United States / Haiming Liu -- Understanding Chinese American transnationalism during the early twentieth century : an economic perspective / Yong Chen -- Republicanism, Confucianism, Christianity, and capitalism in American Chinese ideology / Shehong Chen -- Teaching Chinese Americans to be Chinese : curriculum, teachers, and textbooks in Chinese schools in America during the exclusion era / Him Mark Lai -- Writing a place in American life : the sensibilities of American-born Chinese as reflected in life stories from the exclusion era / Xiao-Huang Yin.
Includes bibliographical references (pages 237-273) and index.
Print version record.
English.
JSTOR
Keywords: Chinese Americans -- Ethnic identity; Chinese Americans -- History; Transnationalism; United States -- Emigration and immigration -- Social aspects; Américains d'origine chinoise -- Identité ethnique; Américains d'origine chinoise -- Histoire; Transnationalisme; États-Unis -- Émigration et immigration -- Aspect social; SOCIAL SCIENCE -- Ethnic Studies -- Asian American Studies; SOCIAL SCIENCE -- General; Chinese Americans; Chinese Americans -- Ethnic identity; Emigration and immigration -- Social aspects; Transnationalism; United States; History